Migratory flights and local wintering movements of Greylag Geese Anser anser in western Europe. Issue 2 (3rd April 2019) - Boos, Mathieu; Nesterova, Anna P.; Chevallier, Damien; Follestad, Arne
ABSTRACT: The local and migratory movements of Greylag Geese Anser anser wintering in southwest and northwest Europe were revealed with global positioning system tracking. Geese in the southwest had smaller home ranges than those from the northwest, and birds also moved large distances over wintering grounds and showed flexibility in the annual choice of wintering sites.